Simulation in Healthcare Supply Chains with Perished Products - Sudeep S. K.; Harshitha H. M.; Akshith R.; Vinay Dravid; Pranav L. R. (International Journal of Innovative Science and Research Technology, 2026)
Perishable healthcare products such as vaccines, blood products, biologics and temperature sensitive medicines incur high supply chain costs under limited shelf life due to uncertain demand with stringent storage requirements during transport. However, a type of approach is to analyze and enhance the operation via simulation-based methods without affecting the real-world systems. This paper presents an overview of studies that implemented simulation techniques in the healthcare supply chains for perishable products linking inventory optimization, cold-chain logistics, waste elimination and service-level improvement. The study uses discrete event simulation which models the movement, storage and consumption of perishable health care products through many supply chain stages which include suppliers, distribution centers, hospitals, and pharmacies. We look at key variables which include demand variability, lead times, spoilage rates, and storage capacity to see how the system performs in different operational settings. What we found isthat which which optimized replenishment policies, dynamic routing, and real time monitoring greatly reduce product waste at the same time that we maintain product availability and patient safety. Results present that health care organizations which implement predictive analyticsin to their simulation modelssee great benefit in terms of improved decision making which in turn they use to predict shortfalls, reduce waste at point of expiry, and better respond in emergency or pandemic situations. Also we see in our study that which digital technologies play a key role in this we look at IoT enabled cold chain monitoring and data driven inventory management.